Functional Analysis of GSTK1 in Peroxisomal Redox Homeostasis in HEK-293 Cells - Cláudio F. Costa; Celien Lismont; Serhii Chornyi; Hongli Li; Mohamed A. F. Hussein; Hans R. Waterham; Marc Fransen (MDPI AG, 2023)
Peroxisomes serve as important centers for cellular redox metabolism and communication. However, fundamental gaps remain in our understanding of how the peroxisomal redox equilibrium is maintained. In particular, very little is known about the function of the nonenzymatic antioxidant glutathione in the peroxisome interior and how the glutathione antioxidant system balances with peroxisomal protein thiols. So far, only one human peroxisomal glutathione-consuming enzyme has been identified: glutathione S-transferase 1 kappa (GSTK1). To study the role of this enzyme in peroxisomal glutathione regulation and function, a GSTK1-deficient HEK-293 cell line was generated and fluorescent redox sensors were used to monitor the intraperoxisomal GSSG/GSH and NAD+/NADH redox couples and NADPH levels. We provide evidence that ablation of GSTK1 does not change the basal intraperoxisomal redox state but significantly extends the recovery period of the peroxisomal glutathione redox sensor po-roGFP2 upon treatment of the cells with thiol-specific oxidants. Given that this delay (i) can be rescued by reintroduction of GSTK1, but not its S16A active site mutant, and (ii) is not observed with a glutaredoxin-tagged version of po-roGFP2, our findings demonstrate that GSTK1 contains GSH-dependent disulfide bond oxidoreductase activity.